A Comparative Study of the Impact of Theta-Burst and High-Frequency Stimulation on Memory Performance - Zhu, Yating; Wang, Rubin; Wang, Yihong (Frontiers in Human Neuroscience, 2016)
The transformation of the information stored in the working memory into the system of long-term memory depends on the physiological mechanism, long-term potential (LTP). In a large number of experimental studies, theta-burst stimulation (TBS) and high-frequency stimulation (HFS) are LTP induction protocols. However, they have not been adapted to the model related to memory. In this paper, the improved Camperi-Wang (C-W) model with Ca2+ subsystem-induced bi-stability was adopted, and TBS and HFS were simulated to act as the initial stimuli of this working memory model. Evaluating the influence of stimuli properties (cycle, amplitude, duty ration) on memory mechanism of the model, it is found that both TBS and HFS can be adopted to activate working memory model and produce long-term memory. Moreover, the different impacts of two types of stimuli on the formation of long-term memory were analyzed as well. Thus the importance of this study lies firstly in describing the link and interaction between working memory and long-term memory from the quantitative view, which provides a theoretical basis for the study of neural dynamics mechanism of long-term memory formation in the future.